Behavioural based safety to reduce accident rates in Raura mining company - Chamorro Celis, Wilder Beto (2024)
The objective of the study was to improve the safety management system through the implementation of behavioural safety in order to reduce the accident rate in the Raura mining company. In terms of methodology, an applied quasi-experimental design was used with a quantitative approach at a descriptive level, using survey and observation techniques, the information was collected through the use of observation booklets and questionnaires. The study population and sample consisted of 80 workers. The results, when comparing the statistical data of 2022 and 2023, a reduction in the number of accidents and incidents was achieved, indicating a significant decrease in the number of accidents by 73%, with the implementation of the SBC methodology, very positive results have been obtained by educating, training and training workers, increasing their level of knowledge and awareness of safety. Also, the trends show an increase of 89.4% in safe behaviours and a decrease of 10.7% in risky attitudes. It is concluded, the SBC methodology has a significant impact, changing risky behaviour to safe behaviour helps to prevent and reduce accidents.